The Effects of Corporate Social Responsibility on Corporate Financial Performance of Chinese Listed Manufacturing Companies - Li, Weimin (2019)
CSR practice has become a worldwide phenomenon that has no longer been limited to traditional individual enterprises. It is an increasingly important part of corporate governance strategy in listed companies. This paper investigates the impacts of CSR on CFP of Chinese listed manufacturing companies by using the panel data from 145 listed manufacturing companies between 2013 and 2017 with the fixed effects models to examine the CSR-CFP link. Based on stakeholder theory, the study used the total CSR index and the score of five different sub-level by HEXUN website. The five different sub-level are shareholders, employees, suppliers and customers, environmental, social scores. In addition, the CFP of this study combined the return on asset (ROA) and Tobin's Q for financial performance measurement, which is a combination of accounting-based performance and market-based performance.